Scientific computing with Scala : learn to solve scientific computing problems using Scala and its numerical computing, data processing, concurrency, and plotting libraries /: learn to solve scientific computing problems using Scala and its numerical computing, data processing, concurrency, and plotting libraries. (2016) - Janc̆auskas, Vytautas
No abstract available